MOBILISASI SUMBER DAYA DAN PARTISIPASI PUBLIK DALAM GERAKAN FILANTROPI ISLAM: Studi pada LAZIS Muhammadiyah di Kecamatan Kalasan, Sleman - Sitti Harnia; M. Falikul Isbah (Program Studi Sosiologi Agama Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2021)
There has been much progress achieved by development in all aspects of human life. However, it is the fact that many layers of the society are left behind the development progress for various reasons. In addition to government’s role, the role of non-state actors like Islamic philanthropic organisations in addressing the problem looks more significant in recent times. Previous studies have explored various aspects of Islamic philanthropic movement, especially in Indonesia. This article focuses on forms of program and mobilization strategy of resources and public participation. Data in this article was collected through a fieldwork on the philanthropic activities of Lazis Muhammadiyah in Kalasan, Sleman, DIY. This Lazismu conducted various empowerment programs, such as house rebuilding, building food stall for those who need a job, education for children through scholarship and parenting in orphanage. This study finds that creating a room of participation for the program beneficiaries and the people around them is the key for effectiveness and efficiency of a philanthropic movement. Participation can be pushed from the stage of planning, executing, and maintaining an empowerment program.The synergy between organisational missions and community solidarity makes the mobilisation of resources and public participation relatively easier.